On Health Policy and Management (HPAM): Mind the Theory-Policy-Practice Gap - David Chinitz; Victor G Rodwin (Kerman University of Medical Sciences, 2014)
We argue that the field of Health Policy and Management (HPAM) ought to confront the gap between theory, policy, and practice. Although there are perennial efforts to reform healthcare systems, the conceptual barriers are considerable and reflect the theory-policy-practice gap. We highlight four dimensions of the gap: 1) the dominance of microeconomic thinking in health policy analysis and design; 2) the lack of learning from management theory and comparative case studies; 3) the separation of HPAM from the rank and file of healthcare; and 4) the failure to expose medical students to issues of HPAM. We conclude with suggestions for rethinking the field of HPAM by embracing broader perspectives, e.g. ethics, urban health, systems analysis and cross-national analyses of healthcare systems.